An evolutionary theory of large‐scale human warfare: Group‐structured cultural selection. Issue 2 (4th March 2015) - Zefferman, Matthew R.; Mathew, Sarah
Abstract : When humans wage war, it is not unusual for battlefields to be strewn with dead warriors. These warriors typically were men in their reproductive prime who, had they not died in battle, might have gone on to father more children. Typically, they are also genetically unrelated to one another. We know of no other animal species in which reproductively capable, genetically unrelated individuals risk their lives in this manner. Because the immense private costs borne by individual warriors create benefits that are shared widely by others in their group, warfare is a stark evolutionary puzzle that is difficult to explain. Although several scholars have posited models of the evolution of human warfare, 1 2 3 4 5 6 these models do not adequately explain how humans solve the problem of collective action in warfare at the evolutionarily novel scale of hundreds of genetically unrelated individuals. We propose that group‐structured cultural selection explains this phenomenon.